Metabolomics: An Emerging Tool for Precision Medicine - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Metabolomics is a developed technology that comprehensively analyzes the metabolites in biological specimens. It appears to be a prospective method in the practice of precision medicine.CONTENT: Metabolomic technologies currently surpass beyond the traditional clinical chemistry techniques. Metabolomic is capable to perform a precise analysis for hundreds to thousands of metabolites, therefore provide a detailed characterization of metabolic phenotypes and metabolic derangements that underlie disease, to represent an individual’s overall health status, furthermore to discover new precise therapeutic targets, and discovery of biomarkers, either for diagnosis or therapy monitoring purpose.SUMMARY: Adequate data processing and quantification methods are still needed to be developed to boost integrated -omics as a powerful clinical practice platform.KEYWORDS: metabolomic, precision medicine, phenotyping, biomarker, nutritional pattern